INTEGRATING HIGH-RESOLUTION GRAVITY GRADIENTS AND 3D INVERSION MODELING TO DELINEATE MINERAL RESOURCES IN THE LEWA DISTRICT, EAST SUMBA, INDONESIA - Raja, Aprianus; Tanesib, Jehunias; Lapono, Laura A. S.; Lewerissa, Richard (Universitas Mataram, 2025)
Research in Lewa District, East Sumba Regency, Indonesia, aimed to identify mineral potential and clarify subsurface geological structures through gravity gradient analysis and 3D inversion modeling. This approach addresses the limitations of field gravity data in the study area. The gravity gradient method was chosen to delineate geological structure boundaries (such as formation contacts and faults) compared to conventional gravity methods and for processing global satellite data (GGMplus and EGM2008 derivatives of ERTM 2160) with limited measured data. Gravity gradient analysis, including vertical, horizontal gradient, and tilt angle, was applied to Complete Bouguer Anomaly data using 2D Fourier transformation. Gravity field correction in Lewa showed positive anomalies from volcanic basement rocks. The gradient analysis sharpened boundaries of anomalies linked to geological structures. Zero contours of vertical gradient and tilt angle defined structural boundaries, while peaks of horizontal gradient and tilt angle indicated metallic mineral sources. 3D gravity inversion modeling (density 2.22â€“2.97 g/cmÂ³) showed rock intrusions at 215 meters depth, interpreted as key to mineralization formation. The 2D sections (A-A', B-B', C-C') contain Masu Formation volcanic rocks, with fault zones filled by Waikabubak Formation sedimentary rocks and silicified rocks from magma intrusion alteration. Fault systems were identified through vertical gradient extremes, representing contact formation. Highly positive contour values on the tilt angle map confirm the influence of the volcanic basement rock. Metal mineralization is closely related to tectonic activity and alteration from massive igneous intrusion. The integration of gravity gradient analysis and 3D inversion modeling has proven to be effective in mapping geological structures and identifying mineral prospects using limited data. These findings provide insights into the subsurface geology of Lewa and provide a basis for further mineral exploration in East Sumba.